Pattern of secondary sexual development of elementary school female students in Yogyakarta Municipality - Anik Puryatni, Anik Puryatni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Adolescence is a part of the growth cycle, characterized by significant changes in physical, cognitive and psychosocial aspects. Improvement in nutritional status and the influence of sexual hormons in the adolescent period cause an acceleration in maturation and the emerging of secondary sexual characteristics.Objective: To examine the beginning of secondary sexual development in female students of elementary school in Yogyakarta Municipality, and the correlation of nutritional status and secondary sexual development.Design: Cross sectional.Materials and methods: Subjects consist of 250 female students, through proportional population multi stage random sampling from all elementary school students in Yogyakarta. The age of menarche and the secondary sexual characteristics were determined using standardized questionaire. Nutritional status was determined based on z-score of body weight to age, body height to age, and body mass index (BMI). Results: The average age of the beginning of mammary enlargement was 11.35 years, and the start of pubic hair growth happened at 11.12 years of age. A larger proportion of the students (70.4%) had not experienced menarche yet, and the average age of menarche was 11.16 (ÃÂ± 0.95) years old. Most of the students had good nutritional status (88%) and normal body height (90%) based on the z-score, and can be categorized as normal based on the BMI (58%). Mammary growth was faster in students with better nutritional status based on body weight/age (p=0.0001), on body height/age (p =0.0002), and based on BMI (p=0.0005). The same result was observed on pubic hair growth of students with better nutritional status: p =0.043 based on body weight/age, and p =0.038 based on body height/age. The age of menarche of students with better nutritional status was younger (p =0.015) based on body weight/age, p=0.033 based on body height/age, andÂ p<0.0001 based on BMI; 15.2% students had never received information concerning sexual development, the source of information mostly were parents, school-mates, books or magazines, and the role played by the teachers was still minimal.Conclusion: The average of mammary growth is 1135 years old, and the average age of pubic hair growth was 11.12 years old. And menarche nutritional status has positive influence on the secondarysexual development.Â Key words: female secondary sexual development, menarche, nutritional status